Factors predicting physical activity and healthy nutrition habits among students in Israel. (30th September 2020) - Beck, H; Tesler, R; Moran, D; Kolobov, T; Harel Fisch, Y
Abstract: Background: The World Health Organization has defined school systems as the significant framework for health promotion, because it enables accessibility to most of the child population. Objectives: To examine the association between health promotion policies of school principals and student-level factors that predict health behaviour patterns: physical activity and proper nutrition. Methods: This cross-sectional study is based on data from the HBSC (Health Behaviour in School-Aged Children) survey that included 7, 000 students in grades 6, 8, and 10 in secular and religious public schools and in Arab schools, and about 126 principals. Results: The findings of the study indicate: at the student level boys perform physical activity more frequently than girls (B = 0.80, p < 0.01); with increasing age students from a high socio-economic background are more physically active (B=-0.34, p < 0.01); and students in religious public schools perform less physical activity compared to students in secular public schools (B=-0.37, p < 0.01). At the multi-level, implementation of a policy that encourages physical activity is a predictor of physical activity habits at the student level (B = 0.09, p < 0.05). Moreover, findings show that school nutrition policies (OR = 0.89, p < 0.05) and principals' commitment to health promotion (OR = 1.13, p < 0.01) predict healthy eating habits among students. Findings also indicate that students in the Arab sector consume less healthy food compared to students in public schools (OR = 0.54, p < 0.05). Conclusions: The results of the current study emphasize the importance of implementing health promotion policies in schools among principals to improve students' physical activity and healthy eating habits.